La loi de divergence: Discussion - Tinbergen, J.; Koopmans, Tjalling C.; Marschak, Jacob; Divisia, Francois; Rueff, Jacques; Chait, B. (Econometrica, 1949)
J. Tinbergen, Tjalling C. Koopmans, Jacob Marschak, Francois Divisia, Jacques Rueff, B. Chait, La loi de divergence: Discussion, Econometrica, Vol. 17, Supplement: Report of the Washington Meeting (Jul., 1949), pp. 124-128